Intravenous Insulin Infusion Protocol Compared With Subcutaneous Insulin for the Management of Hyperglycemia in Critically Ill Adults. Issue 9 (September 2019) - Tran, Kenneth K.; Kibert, Jeffery L.; Telford, Evan D.; Franck, Andrew J.
Background: The use of an intravenous insulin infusion protocol (IIP) is recommended for management of hyperglycemia in the intensive care unit (ICU); however, limited evidence of comparison has been made with subcutaneous (SC) insulin regimens.Objective: This study aims to evaluate the safety and effectiveness of an IIP compared with SC insulin regimens in an ICU patient sample since the implementation of an IIP using a computerized clinical-decision support tool.Methods: This investigation was a retrospective cohort study of patients who were treated for hyperglycemia while admitted to any of the ICUs at a Veterans Affairs Medical Center. Patients who were treated with either an IIP or a scheduled SC insulin regimen between May 1, 2015, and May 25, 2016, were included for evaluation.Results: Blood glucose (BG) was within the normoglycemia range (70-180 mg/dL) for 63.0% of the measurements in patients treated with an IIP (n = 171) compared with 45.7% in those treated with SC insulin regimens (n = 121; P < 0.01). Overall, patients managed with an IIP had a lower proportion of hypoglycemic BG measurements (1.2% vs 2.1%, P < 0.01), a lower proportion of hyperglycemic BG measurements (35.8% vs 52.2%, P < 0.01), and a lower mean BG (172.4 vs 194.3 mg/dL, P < 0.01).Conclusion and Relevance: The results of this study suggest that an IIP in a sample of adult ICU patients was associated with better BG control and lower occurrence of hypoglycemia compared with SC insulin regimens.